The autogenous healing of cracks in reactive MgO-based strain-hardening composites - Wang, Hao (2017)
MgO-SHC is a group of fiber-reinforced strain hardening composite made by MgO cement which is found able to exhibit autogenous healing in natural environment without human interference. This paper systematically investigates the influence of single crack width on the efficiency of autogenous healing in MgO-SHC. Specimens with single crack are conditioned under water and CO2 (10% content) cycles. Reloading was subsequently carried out to specimens after autogenous healing. The evaluation of autogenous healing performance is based on the resonant frequency recovery and crack width reduction. The results show that the autogenous healing is highly related to the crack width. It is concluded that specimens with smaller crack width are more likely to get a fully recovery.